What Do Adolescents See on Social Media? A Diary Study of Food Marketing Images on Social Media - Qutteina, Yara; Hallez, Lotte; Mennes, Nine; De Backer, Charlotte; Smits, Tim (Frontiers in Psychology, 2019)
Food marketing influences eating preferences and choices, especially among adolescents, contributing to the rise of overweight, obesity, and other chronic health disorders. Recent social media advancements have provided food marketers with platforms to reach out to many in more personal and authentic ways as compared to classical media advertising. Such personalized and borderless social media platforms allow marketers to easily use owned, paid, and earned (word-of –mouth) marketing strategies, including paid and non-paid influencers to reach younger target audiences. This study therefore aims to explore food messages adolescents (12-18 year old) encounter on social media, and assess these messages for their sources, the presence of core and non-core food, and the marketing strategies employed. To attain an in-depth understanding of the food messages that adolescents are continuously exposed to, we carried out a diary study with 21 Flemish adolescents who took screenshots of food images they encountered on their social media platforms for the duration of one week. A quantitative and qualitative content analysis of 611 images revealed that adolescents are mostly exposed to messages of non-core (67% of images) and branded (49% of images ) food, often (49% of images) presented in association with a social context such as hanging around with friends, eating at restaurants and celebrating with food. Adolescents often encounter branded food images through peers and social media influencers, the majority of which are part of earned (49% of branded images) or paid (40% of branded images) media food marketing. This research provides an in-depth understanding of the social media messages that adolescents encounter on a daily basis and sheds light on food norms typically communicated on social media by marketers, peers, and influencers. Study findings highlight prominent social media food messages that should be tested for their persuasiveness, providing insights for future research that aims to assess the effects of social media food marketing on adolescents. Based on the study findings, we call for relevant policy actions that address current social media marketing strategies targeted at adolescents.